Volume 5: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30370
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of an Aspirated Fan Stage

Abstract: This thesis focuses on the use of aspiration on compressor blade design. The pressure ratio can be significantly increased by controlling the development of the blade and endwall boundary layers. This concept is validated through an aspirated fan stage experiment performed in the MIT Blowdown Compressor Facility. The fan stage was designed to produce a pressure ratio of 1.6 at a throughflow adiabatic efficiency of 89% at a rotor tip speed of 750 ft/s. Aspiration equal to 0.5% of the inlet flow was applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Since the beginning of 2000, researchers at the Massachusetts Institute of Technology(MIT) have been investigating the use of aspiration, which removes the low-momentum flow from boundary layers of blades to increase the pressure ratio per stage and extend the diffusion factor design space for a highly loaded compressor. The first attempt 8,9 was a transport engine aspirated transonic conventional fan stage, rotor plus stator, with a pressure ratio of 1.6 at a tip speed of only 228.6 m/s. More ambitious research had been reported by Kerrebrock et al.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of 2000, researchers at the Massachusetts Institute of Technology(MIT) have been investigating the use of aspiration, which removes the low-momentum flow from boundary layers of blades to increase the pressure ratio per stage and extend the diffusion factor design space for a highly loaded compressor. The first attempt 8,9 was a transport engine aspirated transonic conventional fan stage, rotor plus stator, with a pressure ratio of 1.6 at a tip speed of only 228.6 m/s. More ambitious research had been reported by Kerrebrock et al.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the practical engineering application value, although the performance of a compressor can be further improved by suction flow rates of about 2%, it is to be appreciated that the actual suction flow rate required in experiments is less than that designed by numerical calculation. 18,25,26 As a result, the effects of boundary layer suction and suction slot location on the tandem cascade flow field are discussed with suction flow rate of about 1%.…”
Section: Analysis Of Suction Schemesmentioning
confidence: 99%
“…For example, the aspirated blade technology proposed by Massachusetts Institute of Technology is using the boundary layer suction method to suppress the separation of the suction surface boundary layer of a blade with a high camber turning angle. 46 Watts and Fish 7 concluded that the tubercle leading edge could increase the lift by 4.8% more than an ordinary model when the attack angle is 10°. Miklosovic et al.…”
Section: Introductionmentioning
confidence: 99%